Transformational experiences in young people: the meaning of a safe haven - Pearmain, Rosalind (International journal of children's spirituality, 2005)
What do adolescents find meaningful in their exposure to spiritual education organised by religious or spiritual institutions? A qualitative study of adolescents participating in summer school events organised by the Religious Society of Friends and Sahaj Marg meditation system was carried out and analysed using Interpretative Phenomenological Analysis. Two central themes emerged of ‘safe haven’ and ‘transforming processes’. The meaning of ‘safe haven’ was further examined and related to Gaston Bachelard’s evocation of the primordial sense of home.